ALAT PENDETEKSI PENGECEKAN KEMATANGAN BUAH TOMAT MENGGUNAKAN ARDUINO DENGAN SENSOR WARNA - Ginting, Adi Gunawan; Siyamto, Yuli (LPPM Universitas Putera Batam, 2021)
The development of increasingly sophisticated technology is now not only mastering the young but also has mastered all circles. and not only that technology is now not only used as a medium of information or receiving information but has been used as a business field, namely as online sales, education as a learning medium. Arduino is a new breakthrough in the world of microcontrollers. Arduino is open source and uses Atmel IC output as the main IC and has its own programming language similar to C language. Arduino types such as Arduino Uno, Arduino Nano, Arduino Mini and Mega. Tomatoes are a staple food and a source of agricultural income for the Indonesian people. Tomatoes can be found anywhere, including in the Riau Islands, Batam city. In shopping centers or traditional markets, before buying from farmers, traders check manually to determine the level of ripeness of the tomatoes. The best tomatoes can usually be seen from the color of the tomato skin. Tomatoes that are still fresh, which are ripe on the tree are usually reddish in color and tomatoes that are half-ripe and then left for a few days so that they are ripe are usually orange in color